HUBUNGAN PRAKTIK PERSONAL HYGIENE PEDAGANG DENGAN KEBERADAAN BAKTERI ESCHERICHIA COLI DALAM JAJANAN KUE LAPIS DI PASAR KEMBANG KOTA SURABAYA - Nuraya, Ardini Debilauralita; Nindya, Triska Susila (Media Gizi Indonesia, 2018)
Pathogenic effect of Escherichia coli bacteria could be detrimental to health. The presence of the bacteria makes food unsafe to consumed. Personal hygiene practice of sellers can infl uence the presence of Escherichia coli on food. This cross-sectional study was aimed to analyze the relationship between personal hygiene practice of sellers with the presence of Escherichia coli bacteria on a traditional layer cake. The study involved 29 traditional layer cake sellers in Pasar Kembang Surabaya. The data collection was done by using observation sheet and laboratory tests on samples of traditional layer cakes. Data was analyzed using chi-square statistical test. The results of this study showed the majority of sellers washed their hands before handling food (96.6%), fingernails were clean and short (86.2%) and didn't smoke when handling food (82.8%). All sellers used clean clothes (100%), but talked when handling food (100%), did not wear an apron and tools when handling food (100%). Escherichia coli was found in 44.8% samples. This study showed there was no relationship between personal hygiene practices of sellers with the presence of Escherichia coli bacteria in traditional layer cakes (p > 0.05) in Pasar Kembang.